Pengaruh Kompetensi Sumber Daya Manusia, Sistem Keuangan Desa, Dan Kejelasan Sasaran Anggaran Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kota Denpasar - I Dewa Gede Yoga Sedana; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2023)
Accountability is a basis or principle that must be applied in the village fund management process. Accountability will make the process of managing village funds more transparent. Once accountability is so important, this study was made to look at the factors that can lead to accountability such as Human Resource Competence, Village Financial System, and Clarity of Budget Targets. The total population in this study was 499 people, which were all employees at the Denpasar City repair shop, with 135 of them selected as the research sample. This study concludes that accountability can increase if it is followed by the growth of better human resource competencies, an effectively designed financial system, and clearer budget targets.